Low foliar nitrogen and elevated defensive metabolites in the invasive weed Calluna vulgaris (heather) may impair biocontrol agent performance - Barrett DP; Minor MA; Peterson P; Fowler SV; Subbaraj AK; Lun DJ; Clavijo McCormick A (Springer Nature, 2026)
Introducing insect biocontrol agents to manage invasive plants is an effective and sustainable management option. However, biocontrol agents sometimes fail to establish or are ineffective in the new range. Heather beetle Lochmaea suturalis, (Thomson, 1866) (Coleoptera: Chrysomelidae) sourced from the United Kingdom (UK), was introduced into New Zealand’s North Island Central Plateau (CP) to control invasive Calluna vulgaris (L.) Hull (heather). The beetle was difficult to establish and the few populations that did, achieved poor population growth rates and expansion in contrast to the rapid rates associated with its conspecifics in the UK. We hypothesize that low soil nutrients such as nitrogen and phosphorous (N and P) on the CP may be linked to changes in C. vulgaris’ primary nutritional and secondary defensive metabolites, leading to poor beetle performance. Testing this hypothesis involved application of N and P to soil in C. vulgaris field plots, measurement of foliar N and Carbon (C), plus using non-targeted metabolomics, exploring differences in the primary and secondary metabolites between treatments. Raising soil nutrients amplified several primary metabolites including N-based amino acids and concomitantly reduced the majority of phenylpropanoids, a secondary metabolite group containing many defensive compounds. This work seeks to better understand, how abiotic conditions in a new environment, influence invasive plant metabolism, potentially altering the efficiency of foliage assimilation which may impair biocontrol agent establishment and effectiveness. Such understanding may be applied to mitigate potential foliar deficiencies at release sites and contribute to improving success rates of biocontrol as a management strategy for invasive plants.
Keywords: Invasive plants; Calluna vulgaris; Foliar nitrogen; Metabolomics; Phenylpropanoids; Biological control